Implementation of the teaching campus literacy program 5 through habituation and development as an effort to improve the class AKM of grade V students of SDN 09 Petarukan - Prahestu, Punika Sari; Purwati, Panca Dewi (Universitas Muhammadiyah Malang, 2024)
This study aims to outline the Teaching Campus 5 literacy program's implementation through habituation and development literacy, the challenges encountered during program implementation, and the program's efficacy in enhancing fifth-grade students' literacy skills through class AKM at SDN 09 Petarukan. The research was conducted from February 20, 2023, to June 9, 2023 (during the Teaching Campus 5 period) at SD Negeri 09 Petarukan, Pemalang district. The research method used was qualitative with a descriptive design. Data were collected through observation, class AKM tests before and after the treatment, and documentation. The class AKM test was conducted using a laptop with a unique platform installed, namely Learning Motivation. The average difference in class AKM before and after the habituation and development program treatment was compared using data reduction, data presentation, and conclusion drawing. The research findings describe the program implementation process, the obstacles researchers, students, schools, and parents face, and the impact on improving students' class AKM. With a significant difference between the average pretest result of 31% and the average posttest result of 51%, the results demonstrated that the Teaching Campus 5 literacy program, which uses habituation and development literacy, effectively raised the class AKM of grade V students. With exemplary literacy implementation, students can improve their critical thinking skills, which can positively impact the results of the AKM, which tests students' analysis and synthesis abilities. Therefore, implementing literacy improves students' class AKM results in reading, writing, logical thinking, understanding the subject matter, learning independence, and critical thinking skills, especially in implementing the computer-based National Assessment (ANBK). It can also positively impact teachers and schools in understanding the importance of sustainable literacy learning. It can also provide insights for education policymakers, both at the school and local levels, in developing policies that support literacy development in other primary schools with findings that support improving literacy programs. Therefore, it is recommended that schools consider implementing literacy programs like this to enhance students' grade-level AKM at the primary level. This study has implications for ANBK outcomes in primary schools.